(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The goal of the current research is to measure the economic empowerment of Palestinian women in UNRWA’s community development centers, in light of the difficult living conditions. A methodology appropriate to the goal of the research has been adopted, represented by the descriptive analytical approach, using a sample method. The questionnaire was also used as a tool for collecting data. The original community for the research consisted of female beneficiaries in community development centers, residing in the city of Damascus during the period of the research, and the size of the sample that was taken was 10% of the original community, which amounted to about 500 female beneficiaries, meaning the questionnaire was implemented on 50 female beneficiaries. Based on calculating the number and percentage and analyzing those percentages of the data, a number of results were reached that indicate in their entirety the following: 1-The percentage of Palestinian women’s preferred profession of shaving and beautification in UNRWA’s community development centers reached 40%, which is a good percentage.2- Vocational courses in UNRWA’s community development centers contributed to the empowerment of Palestinian women by a good percentage of 40%.3-Small projects contributed to the empowerment of Palestinian women in UNRWA’s community development centers by an acceptable rate of 26%.4. The low rate of Palestinian women’s awareness of their rights in UNRWA’s community development centers reached 20%.5- The low percentage of Palestinian women learning methods for marketing their projects in UNRWA’s community development centers reached 18%.